APPLICATION of MANUFACTURING SYSTEMS TO CALCULATE PRODUCTION TARGET NEEDS PRIDE CHAIR DESIGN - Imron Rosyadi N R; Matsaini (UNIPA PRESS, 2021)
A process in a company or industry will never be separated from the name of the production, production is an important part of the running of a company or industry. This research aims to provide input to the company to be able to calculate the need for future production targets based on previous production data so that the company can prepare all production needs. Production can also be interpreted as an activity to increase the use of goods and benefits in fulfilling daily activities. In practice, a person or business entity that carries out production activities is called a producer. Producers produce goods to be sold to meet the needs of others and theirindividuals. Production activities, there is an activity of processing raw materials into semi-finished materials, and then proceeding from semi-finished materials to finished materials. Therefore, a separate focus is needed to determine the amount of production, output, and input that is done. One thing that can be done is knowing up to calculating the needs of all processes to the production target. While the focus of production activities from the production system to inventory is First, forecasting is important and foremost. Second, inventory control is very important in the production system for inventory, especially in planning the purchase and delivery of raw materials and components. Third, the production of large quantities of inventory items is more structured.